2004
DOI: 10.1111/j.1365-2249.2004.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

TSH receptor-adenovirus-induced Graves’ hyperthyroidism is attenuated in both interferon-γand interleukin-4 knockout mice; implications for the Th1/Th2 paradigm

Abstract: SUMMARYThe role of the Th1/Th2 balance in the pathogenesis of murine Graves' hyperthyroidism is controversial. In BALB/c mice injected with adenovirus expressing TSH receptor (TSHR-adeno model), we found that suppression of TSHR-specific Th1 immune responses by exogenous interleukin-4 (IL-4), agalactosylceramide or helminth ( Schistosoma mansoni ) infection was associated with inhibition of hyperthyroidism, indicating the critical role for Th1 cytokines. In contrast, BALB/c IL-4 knockout (KO), but not interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
0
23
1
1
Order By: Relevance
“…For example, mice genetically deficient for a certain cytokine are useful for this purpose. Indeed the experiments with mice deficient for IFN-g (a Th1 cytokine) or IL17 (a Th17 cytokine) have revealed a critical role played by IFN-g, but not IL17, in developing experimental Graves' hyperthyroidism in a susceptible BALB/c mice (Nagayama et al 2004a, Horie et al 2010. This study identified IL10 as another important cytokine for the pathogenesis of Graves' disease in mice.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For example, mice genetically deficient for a certain cytokine are useful for this purpose. Indeed the experiments with mice deficient for IFN-g (a Th1 cytokine) or IL17 (a Th17 cytokine) have revealed a critical role played by IFN-g, but not IL17, in developing experimental Graves' hyperthyroidism in a susceptible BALB/c mice (Nagayama et al 2004a, Horie et al 2010. This study identified IL10 as another important cytokine for the pathogenesis of Graves' disease in mice.…”
Section: Discussionmentioning
confidence: 84%
“…Although the reason(s) for this difference is unclear, it is not surprising that the pharmacological levels of exogenous IL10 and the physiological levels of endogenous IL10 have distinct functions, as we have previously shown for IL4 (Nagayama et al , 2004a.…”
Section: B Cells In Il10mentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, the background of H. pylori prevalence influences the positive predictive value (PPV) of this method, as discussed in the study by Soveid in Iran. [15][16][17][18][19][20][21][22] We found no significant association between H. pylori seropositivity and Graves' disease in this subgroup, as shown by the pooled OR of 3 studies using serology method, and moderate heterogeneity. In contrary, the association was statistically significant in the non-serology method subgroup with 0% of heterogeneity.…”
Section: Total (95% Ci)mentioning
confidence: 78%
“…В результате эксперимента было также доказано, что доста-точно кратковременное изменение уровня ТГ со-провождается дисбалансом в концентрации ос-новных предикторов амплификации иммунного ответа. Зафиксированная динамика может сви-детельствовать о ключевой роли ТГ в сохранении баланса Th1-/Th2-и Тreg-цитокинов, т. к. сдвиг уровня сывороточных оппозитных цитокинов был ответом на изменение тиреоидного статуса, что не противоречит результатам предшествую-щих исследований [14].…”
Section: Zdor Vv Et Al здор вв и др Medical Immunology (Russia)unclassified